Mapping and analysing historical indicators of ecosystem services in Germany. (April 2017) - Dittrich, Andreas; von Wehrden, Henrik; Abson, David J.; Bartkowski, Bartosz; Cord, Anna F.; Fust, Pascal; Hoyer, Christian; Kambach, Stephan; Meyer, Markus A.; Radzevičiūtė, Rita; Nieto-Romero, Marta; Seppelt, Ralf; et al.
Highlights: Historical service provisioning aids understanding of today's land-use patterns. Provisioning services appreciated in the past are partly fostered by subsidies today. Diversity of historical ecosystem services is explained best by precipitation. Livestock-keeping and mixed farming co-occurred with high service richness. Abstract: In recent ecosystem service studies, historical data have gained importance as basis for analysing temporal trends and for adapted land management strategies; however, the total number of such studies remains small. Contributing to recent efforts, the primary objective of this study was to assess local ecosystem service products historically used in Germany and to link their distribution patterns to environmental gradients and traditional land-use systems. From maps and detailed regional descriptions of regionally distinct historic farmsteads, building materials used and village types we extracted information on ecosystem service products appropriated in 1950 and before. A spatial model was used to test the derived ecosystem service diversity against topo-climatic conditions. Regional service richness was further compared to the type of traditional land-use system (i.e. focus on crops, focus on livestock or mixed systems). We were able to identify hot spots of historical ecosystem service provisioning in Northern and Southern Germany, whereas significantly lower service numbers were recorded in Eastern Germany. The strong spatial differences in the diversity of historical service products could be explained best by (high) precipitation during the vegetation period. Furthermore, traditional livestock keeping, which relied on various fodder sources and fertilisation techniques to improve poor soil quality, and mixed systems mostly co-occurred with higher regional ecosystem service richness. The baseline of historical ecosystem service provisioning analysed here aids our understanding of current land-use patterns in Germany. Furthermore, a change of perception for specific landscape elements became apparent from our analyses. For example, hedges planted to separate livestock and to provide fuel in the past are today appreciated as important elements for biodiversity conservation. Furthermore, our study helps to preserve knowledge about locally sourced ecosystem services thereby increasing the understanding of cultural landscapes which may help to maintain their remnants.